RELATIONSHIP MARKETING AS A MODERN MARKETING CONCEPT - VASILCHENKO, Oleksiy; ILIENKO, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the concept of "relationship marketing" and provides its interpretation by scientists. The authors analyzed the stages of the evolution of relationship marketing in Ukraine from the initial attempts of its implementation to modern complex strategies based on the latest technologies and approaches. It is proven that relationship marketing marks a radical change in the paradigm of marketing worldview, which is characterized by the transition from competition and conflict to interdependence and cooperation, and new practices according to the principles of classical marketing tools are given. The work analyzes the main principles of relationship marketing, such as personalization (allows companies to better understand the needs and preferences of their customers), individual approach (the emphasis is on personal interaction with the customer), trust (formed through transparency, honesty and reliability in the company's interaction with customers) and communications (ensure constant communication between the company and clients). The differences between transactional marketing, which is aimed at ensuring a one-time sale from a large number of customers, and relationship marketing, which is aimed at encouraging repeat purchases from a certain pool of consumers, are presented. The path of customers is analyzed - from potential consumers to reliable consumers, some of whom, with active interaction with the company, will grow into partners of the company. The authors consider the role of technology and digital tools in the implementation of this concept, including the use of e-mail (with personalized letters companies can inform customers about new products, special offers and promotions, as well as remind them about important events or dates), social networks (allow not only to inform customers about new products and services, but also actively interact with them, receive feedback and build trusting relationships), customer relationship management (provide the opportunity to collect, store and analyze information about customers, their preferences, purchase history and interaction with the company). It also explores the benefits and challenges of moving to a relationship marketing model, and provides recommendations for businesses seeking to implement the concept.
Keywords: relationship marketing; potential customer; partner; CRM; personalization; customer loyalty; digital tools